La Fornarina y el origen de la Canción Española / La Fornarina and the origins of the song in Spain - Barreiro, Javier (Asparkía. Investigació feminista, 2013)
RESUMEN La melodramática biografíaqde La Fornarina pone en el tapete un buen número cuestiones candentes en los tres primeros lustros del siglo xx: la configuración de un nuevo género musical -la llamada canción unipersonal-, la ascensión social de la mujer junto a sus dificultades por configurar una sexualidad libre, la miseria de las capas populares españolas, las muchas caras de la prostitución, los cambios en la sociabilidad, que alumbrarán nuevas formas de diversión y espectáculo en los ámbitos urbanos y darán lugar al éxito arrollador de las varietés . . . La Fornarina representó en el imaginario de la España primisecular el primer mito erótico popular, al tiempo que se constituía en imagen de la modernidad para muchos intelectuales que la aclamaron y adoraron. Palabras clave: Fornarina, canción, prostitución, varietés y modernidad. ABSTRACT The melodramatic biography of La Fornarina raises a large number of the burning issues of the first fifteen years of the 20th century: the establishment of a new musical genre -the so-called one-person song- the social ascent of women, together with their di"cu1ties in establishing sexual freedom, the extreme poverty of the lower levels of Spanish society, the various faces of prostitution, the changes in social life that would give rice to new forms of entertainment and shows in urban settings and would result in vaudeville ... In the Spanish imagination at the beginning of the century, La Fomarina represented the first popular erotic myth, and an image of modernity for many intellectual people who acclaimed and adored her. Key words: Fornarina, song, prostitution, vaudeville and modernity.